ISLAM: MEMBENTUK SAINS DAN TEKNOLOGI - Danusiri, Danusiri (Jurnal THEOLOGIA, 2015)
Abstract: The establishment of science-technology Islam originated from the transcendental consciousness that God acts directly provide instruction to people in his capacity as al-'Alim and al-Mu'allim al-NÄs with inspiration pattern into intuition or follow the instructions of the Quran on the basis of faith in the verses relating to science-technology. God teaching techniques outlined by humans with the conceptualization, theorization, saintifikasi, and technologization the verses of Allah either paragraph quraniyyah and kauniyyah. Starting point is the establishment of science-technology read. Results of reading will get something, a concept, or a variable. Thus, the more the reading of a Muslim will increasingly have something, concepts or variables. If the reader can find the basic relationship of two or more things, concepts, variables, then he can find one unit theory. Segususan systematic theory will result in one branch of science. Human intellectual activity that knows no stopping, then starting from only one branch of science will continue to be found various kinds of science. The next route, childbirth science technology. And, science-technology school of Islam embraced the benefits of technology for the service in order to obtain mará¸atillah. Abstrak: Rute pembentukan sains-teknologi Islam berawal dari kesadaran transendental bahwa Allah berperan langsung memberikan pengajaran kepada manusia dalam kapasitasnya sebagai al-â€˜Alim dan al-Muâ€™allim al-nÄs dengan pola pengilhaman ke dalam intuisi atau mengikuti petunjuk al-Quran atas dasar iman dalam ayat-ayat yang berkaitan dengan sains-teknologi. Teknik pengajaran Allah dijabarkan oleh manusia dengan jalan konseptualisasi, teorisasi, saintifikasi, dan teknologisasi terhadap ayat-ayat Allah baik ayat quraniyyah maupun kauniyyah. Dan, sains-teknologi Islam menganut mazhab manfaat teknologi untuk ibadah dalam rangka memperoleh mará¸atillah. Keywords: konsep, teori, sains, teknologi, mará¸atillah.